ポストコロニアル台湾の「親日言説」と帝国の記憶の再生 ― 主体性と共犯性のはざまで - 아마에 요시히사 (한림일본학 (구 한림일본학연구), 0(40), 2022)
ポスト帝国での帝国の記憶はポストコロニアルの土地の人々との交流の中で形成されるといえる。 本稿では、1990年代の民主化以降、台湾で出現した数々の親日現象及びそれが創出する「親日言 説」と日本人の帝国の記憶の関係について検証する。親日現象として主に次の三つのケースに着目 する。１）日本統治時代の建築物の修復、保存と再生、２）戦前台湾で生まれ育った日本人（「 湾生」と呼ばれる）の「回家」（ふるさと帰郷）運動、そして３）ポピュラー文化における日本統治下 の台湾の記憶表象である。これらの代表的かつ象徴的な事象は、メディアを通じて日本でも広く知ら れるところとなったため、親日台湾言説の再/生産に貢献した。日本では、しばし「植民地にしたにも 関わらず日本に好意的でいてくれている」とか、日本統治時代の建造物を大切に保存している様子 から「植民地統治を肯定的にとらえて入れている」と一面的に解釈されがちであるが、そこには中国か ら独立した民族（ネーション）を想像するために日本統治時代の記憶を積極的に活用しようとする政 治力学が働いていることはあまり知られていない。これは民主化されるまで戦後長いこと、日本時代 の記憶が公的空間において国民党政府主導の抗日ナラティブに支配されていたことに対する民衆の 反動であるわけである。したがって、日本時代の記憶の再生は自分の歴史を取り戻すという台湾人 の主体性の実践であると同時に、その過程で植民地帝国をノスタルジックに語る風潮ゆえに、帝国 主義の罪を過小視し、美化する危険性をも孕んでいるといえる。 Since its democratization in the 1990s, Taiwan, a former Japanese colony (1895-1945), has transformed into one of the most pro-Japan nations in the world. Besides the plethora of Japanese commodities, food, and images in everyday space, the nation’s love for Japan extends to things relating to its colonial past. In exploration of the relationship between pro-Japan discourse in Taiwan and how contemporary Japanese people remember their imperial past, this article investigates the following three cases: 1) the restoration, conservation, and regeneration of structures built in Taiwan during the Japanese colonial period; 2) the homecoming of Japanese born in Taiwan before 1945 (known as wansei); and 3) the consumption of memories of colonial Taiwan in contemporary Taiwanese popular culture. These social and cultural phenomena, after becoming widely known to the Japanese people via mass media—both mainstream and social—have contributed to the production of a d iscourse i n Japan in w hich T aiwan is p erceived a s a pro-Japan nation (sinnichi kokka). While Japanese people tend to think that the Taiwanese have favorable feelings for Japan despite 50 years of colonial rule, and they interpret the preservation of Japanese colonial heritage as well as consumption of memories of Taiwan’s colonial past as a sign of Taiwanese people’s nostalgia, they tend to overlook Taiwanese people’s political motivations: Taiwanese are appropriating their memories of the Japanese past as their own since they desire to be considered independent of China. The article argues that while pro-Japan phenomena should be celebrated as a practice of both a burgeoning democracy and Taiwanese subjectivity, one should also be aware of the danger of romanticizing Japanese imperialism, as well as inflicting added pains on the victims of colonialism as a result. KCI Citation Count: 0